Perancangan Hybrid System PLTS dan Generator Sebagai Catu Daya Tambahan Pada Tambak Udang Vaname: Studi Kasus Politeknik Keluatan Dan Perikanan Kupang - Nugraha, I Made Aditya; Desnanjaya, I Gusti Made Ngurah; Serihollo, Lukas G. G; Siregar, Jhon Septin M. (Majalah Ilmiah Teknologi Elektro; Vol 19 No 1 (2020): (Januari - Juni ) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2020.v19i01.P18, 2020)
This reaserch discusses the design of the Hybrid System between Solar Power Plant and Generator as an additional power supply that will be carried out on the Shrimp Vanamei pond. This system will produce electrical energy needed in the cultivation of Vanamei Shrimp, both hatchery and enlargement activities. The use of solar power plants as one form of exploiting the potential of solar energy that is so large in East Nusa Tenggara and the lack of reliability of the electricity network. Based on the PV specifications that will be designed, in a day solar power plant can produce energy of 58.76 kWh, and can meet the electrical energy needs of all Vanamei Shrimp ponds. If in cloudy conditions and the energy produced by solar power plant is insufficient then a generator can be used as a substitute energy source.